(untitled) (Islas, 2021)
Este trabajo profundiza en una arista poco investigada del pensador cubano Enrique José Varona: sus ideas estéticas. Toma como hilos conductores dos núcleos temáticos fundamentales: Primeramente aborda los principios básicos del humanismo en la modernidad. Seguidamente introduce la comprensión filosófica de simpatía; señala un grupo de connotaciones éticas y estéticas de esta categoría en el pensamiento occidental de los siglos xviii y xix. Con respecto al pensamiento de Enrique José Varona, se determinan rasgos humanistas en su reflexión estética, en relación con el contexto occidental y cubano. Se valora el papel de la concepción de simpatía de Varona en el conjunto de sus ideas estéticas, y en el contenido humanista de las mismas. Se analiza la relación entre la educación estética, la simpatía y la moral. This research goes more deeply into an aspect of Enrique José Varona, which has little been researched: his aesthetic ideas. The paper is based on two main topics. First, it focuses on humanism and its main principles, as a set of ideas which stress the human being dignity and the search of its harmonic development. Later, the paper presents the philosophical understanding of sympathy, and shows a group of ethical and aesthetic connotations of such category in the Western thinking of 18th and 19th centuries. With respect to Enrique José Varona´s thought, some humanistic features are determined in his aesthetic ideas, related to the Western and Cuban context. The role of Varona´s sympathy concept with his aesthetic ideas as well as their humanistic content is assessed. The relationship among aesthetic education, sympathy and ethical values is also studied.